2016
DOI: 10.1212/wnl.0000000000002976
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anesthetic management during intra-arterial therapy for acute stroke in MR CLEAN

Abstract: This study provides Class II evidence that for patients with acute ischemic stroke undergoing IAT, mRS scores at 90 days improve only in patients treated without GA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
4
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(172 citation statements)
references
References 19 publications
4
156
4
2
Order By: Relevance
“…Endovascular thrombectomy using a stent retriever is considered an efficient method for blood flow restoration in patients with ischemic stroke due to large intracranial vessel occlusion (1)(2)(3)(4)(5). However, failure of reperfusion persists in a subset of patients due to various factors, such as ICAS (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endovascular thrombectomy using a stent retriever is considered an efficient method for blood flow restoration in patients with ischemic stroke due to large intracranial vessel occlusion (1)(2)(3)(4)(5). However, failure of reperfusion persists in a subset of patients due to various factors, such as ICAS (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, five randomized trials showed improved efficacy of endovascular thrombectomy compared with standard medical care in patients with acute ischemic stroke (AIS) caused by arterial occlusion in proximal anterior circulation (1)(2)(3)(4)(5). This procedure is considered the standard of care for patients with proximal anterior circulation occlusions (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of general anaesthesia was associated with less favourable outcome compared with sedation in a non-randomised, post-hoc comparison and further trials are in progress to address this question. 25 Puncture site complications, such as hematoma or haemorrhage, can occur. 26 Relevant procedural complications reported in the MR CLEAN trial included 5.2% excess incidence of new ischemic stroke in a different vascular territory, embolisation into new territories outside the target downstream territory of the occluded vessel in 8.6%, procedure-related vessel dissections in 1.7% and vessel perforations leading to subarachnoid or intracerebral haemorrhage in 0.9%.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The survival is associated with incomplete MCA territory involvement and atherosclerosis origin (85). Endovascular studies have noticed that patients who require general anesthesia have worse functional outcomes at 90 days versus those who do not require general anesthesia as part of their acute care (86).…”
Section: Airway and Ventilationmentioning
confidence: 99%